Mitochondrial Redox Regulations and Redox Biology of Mitochondria - Ježek, Petr (Antioxidants (Basel, Switzerland), 2021)
Mitochondria undoubtedly represent a metabolic hub, but also act as a redox hub, controlling cell fate and emanating superoxide/H2O2, which in a regulated form and timing provide redox signaling [...].